Could the Global Digital Service Providers be Persuaded to Pay Their Share? - Teski, Norbert; Pulay, Gyula (Public Finance Quarterly, 2021)
The emergence, rapid expansion, and globalization of digital services have significantly reshaped the worldeconomy. The rise of global digital service providers, i.e. multinational companies providing digital services in many countries around the world, is also a new challenge in terms of equitable public burden bearing. Under current tax rules, physical presence provides the legal basis for the exercise of each country’s taxing power. However, digital services do not require a physical presence. Taking advantage of this, global digital service providers do not tax their profits where they produce, but where the tax conditions are most favourable. As a result, they contribute much less to public burdens in proportion to their profits than traditional economic actors, and most of the countries concerned lose significant tax revenues. Many international organizations are looking for a solution to this inequitable situation, but no agreement has yet been reached. The solution is complicated by determining where profit-generating value creation occurs geographically. This article reviews the answers to these questions.